Data flow analysis by linear programming model - Armen H. Alaverdyan; Vilik M. Karakhanyan; Vardan R. Tonoyan (Изд-во НАН РА)
The paper presents the general discussion of the data °ow algorithms structuring problem on one hand, and, as an example of that particular problem class, the analysis of the linear programming problem when the objective function coe±cients vary depending on the data flow. The problem is in reconstruction of current result with such an approach, which is the most plain from the full solution of the problem by the dynamic data set flow.
Keywords: Mathematics; Computer software